2012
DOI: 10.1136/bjophthalmol-2012-302289
|View full text |Cite
|
Sign up to set email alerts
|

Staining internal limiting membrane with a mixture of BBG and sodium hyaluronate

Abstract: Visco-BBG can be a useful method to assist macular surgery and can overcome some of the disadvantages of conventional BBG solutions dissolved in BSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is possible that differing concentrations and formulations of BBG could alter the staining patterns observed. 25 Importantly, this study has provided a direct clinicopathologic correlation between the staining patterns of the ILMspecific dye BBG and ILM vitreous surface tissue. Inner limiting membrane peeling has been shown to improve closure rate in MH surgery.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that differing concentrations and formulations of BBG could alter the staining patterns observed. 25 Importantly, this study has provided a direct clinicopathologic correlation between the staining patterns of the ILMspecific dye BBG and ILM vitreous surface tissue. Inner limiting membrane peeling has been shown to improve closure rate in MH surgery.…”
Section: Discussionmentioning
confidence: 98%
“…These cells were positive for GFAP, suggesting glial cell infiltration. Uemoto et al10 reported that BBG-positive ILM isolated from MH and epiretinal membrane revealed a membrane with few cell infiltration based on pathological analysis. Therefore, the BBG-negative case shown in this report may represent more glial cell infiltration within the ILM tissue than ILM stained with BBG.…”
Section: Discussionmentioning
confidence: 99%
“…While BBG selectively stains the ILM, staining intensity has been reported to be significantly inferior to that of ICG 9 14 15. A number of methods to promote intraoperative BBG sedimentation, such as dye cooling16 and a solution in 4% polyethylene glycol,4 and 5% glucose17 and visco-BBG18 and heavy-water BBG (BBG-D 2 O) have been suggested. However, the only objective measurement of BBG's staining characteristics with CIELAB scores was evaluated for BBG-D 2 O; objective chromaticity scores suggested that ILM staining is not significantly improved with the new formula 9…”
Section: Discussionmentioning
confidence: 99%